Implementasi Pendidikan Sufistik Sebagai Penguatan Moderasi Beragama Di Perguruan Tinggi Melalui Pendidikan Agama Islam - Pratama, M. Arifky; Permatasari, Iin; Herawati, Emy; Irama, Dedi; Suprianto, Miki; Pitriani, Yetri (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This research aims to examine the implementation of Sufistic education as an effort to strengthen religious moderation in higher education. Through a literature study, this research analyzes various aspects related to Sufistic education, ranging from its impact on tolerance, radicalism, to its contribution in building a peaceful society. The results show that Sufistic education has significant potential in shaping the character of students who are religious, tolerant and moderate. The core values of Sufism such as compassion, tolerance, and humility are in line with the principles of religious moderation. Nevertheless, the implementation of Sufistic education still faces various challenges, such as the lack of competent human resources and cultural resistance. This study concludes that Sufistic education can be one of the solutions in overcoming the problem of radicalism and intolerance in Indonesia. However, more systematic and integrated efforts are needed to effectively implement Sufistic education in higher education.